Deep Brain Stimulation Targets, Technology, and Trials: Two Decades of Progress. (August 2016) - Burchiel, Kim J.
Abstract : ABBREVIATIONS: AD, Alzheimer disease DBS, Deep brain stimulation FDA, Food and Drug Administration MER, Microelectrode recording Abstract : Supplemental Digital Content is Available in the Text.